Cacao Seed Purity and Genotype Influence on Seedling Growth under Peasant-Farmer Conditions in Ghana. Issue 5 (2nd September 2016) - Padi, Francis Kwame; Ofori, Atta
ABSTRACT: One of the reasons for the low yields of cacao ( Theobroma cacao L.) in West Africa is the poor adaptation of varieties to a rapidly changing climate reflected in poor seedling survival and reduced precocity. To show the impact of cacao seed purity and genotype on seedling survival and precocity, recommended varieties being supplied to farmers were sampled from four seed gardens and compared with breeders' varieties in one on-station and five on-farm trials in Ghana. Varieties were assessed for plant survival, stem diameter increment and pod production by 27 months after transplanting. Parentage analyses at 75 single nucleotide polymorphism (SNP) loci revealed the presence of illegitimate progeny (seedlings of unapproved parents) among the recommended varieties, with selfed progeny comprising up to 50% of seedlings from one seed garden. The selfed progeny possessed the least vigor, and had not initiated pod production by 27 months after transplanting. In general, the seed garden varieties performed poorly compared with the breeders' varieties for all three traits. On the strength of the results of the present study, two key actions are needed to increase cacao adaptation and yields at the farm level. First, a DNA marker-auditing system of the progenies issued from the seed gardens should be operationalized as a quality-control mechanism. Second, new male parents that produce seedlings of improved vigor need to be introduced into the seed gardens to improve cacao plant survival and yield.